2016
DOI: 10.18632/oncotarget.14112
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of Ki67 in ovarian high-grade serous carcinoma: an 11-year cohort study of Chinese patients

Abstract: ObjectiveThis study sought to assess the prognostic role of Ki67 in primary ovarian high-grade serous carcinoma (HGSC) and to determine whether Ki67 expression can predict responsiveness to platinum and paclitaxel chemotherapy.ResultsA total of 318 women were included in the analysis and the median follow-up time was 48 months (range, 3–150 months). Ki67 proliferation indices ranged from 3% to 95% with a median of 40%. Using 40% as the cut-off value for the Ki67 index, we classified 141 patients as having low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
(31 reference statements)
3
33
1
Order By: Relevance
“…12,40,41 In our study, the Ki67 expression was significantly higher in HGSOC than in LGSOC. In agreement with Chen et al, 40 Feng et al, 12 and Bachmayr-Heyda et al, 41 we observed no relationship among Ki67 expression, stage, residual disease, recurrence, or disease progression. Some studies suggest that high expression of Ki67 is associated with worse survival because Ki67-positive tumors are highly proliferative.…”
Section: Discussionsupporting
confidence: 49%
“…12,40,41 In our study, the Ki67 expression was significantly higher in HGSOC than in LGSOC. In agreement with Chen et al, 40 Feng et al, 12 and Bachmayr-Heyda et al, 41 we observed no relationship among Ki67 expression, stage, residual disease, recurrence, or disease progression. Some studies suggest that high expression of Ki67 is associated with worse survival because Ki67-positive tumors are highly proliferative.…”
Section: Discussionsupporting
confidence: 49%
“…Epithelial ovarian cancer is the most common type of ovarian cancer, which has the highest mortality rate of all gynecological malignancies. This high mortality rate is largely due to the lack of an effective biomarker; in addition, it is difficult to diagnose patients at the early stage of the disease and most patients are diagnosed at advanced stages (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed that there were some reports on the survival prediction model of patients with EOC [6][7][8][9][10], while the recurrence prediction model of patients with EOC is relatively less [11]. In this study, the in uencing factors related to the recurrence of EOC were screened out and evaluated by mathematical methods.…”
Section: Discussionmentioning
confidence: 99%